Oficinas pedagógicas de trabalho cooperativo: uma proposta de motivação docente - Antunes, Denise Dalpiaz (2012)
Human life is full of challenges, desires and opportunities. Each individual has the ability to make his or her choices for personal reasons. The educator, a human being in his or her adulthood, sets in constant development, the need for self-knowledge in pursuit of their academic ideals. In this way, the research project presented here shows the necessary indicatives for the self-realization of teachers, which aimed to answer the question: How Cooperative Pedagogical Workshops (OPTC) can contribute to a more humane continuous training and motivating self-knowledge? Assuming sustained Cooperative Pedagogical Workshops set themselves a proposal of teacher motivation in continuous education, which can promote self-knowledge, in addition to finding the personal reasons that led them to teaching. That is why participation was proposed, through the sharing of feelings, thoughts and proposals for different actions in daily práxis (practice), in OPTC. Active teachers participated from a school in the state teaching network, in the state of Rio Grande do Sul, and in the municipality of Porto Alegre. To this end, this research study of quantitative and qualitative approach, elected within the naturalistic paradigm, the Case Study as a research method, within a single school setting. For the collection of data, a Motivational Indicators in Higher Education Teaching Practice questionnaire (adapted for Basic Education) was used, with respect to the quantitative exploratory-diagnostic study. Regarding the collection and subsequent qualitative analysis, we chose the Journal of Cooperative Pedagogical Workshops, photographic records and tape recorder recordings. After the OPTC we sought to contribute to the accuracy of the survey data with the Evaluative Form and Focus Group. On the investigative way each OPTC, with their goals, indicated categories, which sometimes a priori (in advance), sometimes a posteriori (after the event), forms part of the construct of the whole human being. These, then highlighted are intrinsic and identified the themes of each workshop. They are as follows: Who is the Teacher: adult in constant development, who on the path to self-knowledge must seek self-realization; Who is the Student: human being who brings into the learning environment their personal constructs, those which need to be respected; Self-concept: personal construction, built in social relations that make up the selfimage and self esteem of the individual; Educational Reality: representation of the social environment, which identifies and specifies the cultural indicators for the school environment; Actions and Emotions: feelings pervade human life and need to be established and worked on in the educational environment; Personal Recognition: The teacher, before understanding and perceiving others, needs to know and recognize himself or herself as they are. However, it is argued that participation in the OPTC, primarily indicated in this study, is established as a self-training motivational proposal in continuing education, with opportunities for selfknowledge, thus confirming the thesis of this research.